High Repetition Rate in Ultra-Wideband Radar Systems - O. S. Mironov (Известия высших учебных заведений России: Радиоэлектроника)
Low and high repetition rate work modes for ultra-wideband radar are considered. The ultra-short pulse packs usage for ultra-wideband radar systems is proposed. The advantages, disadvantages and probable fields of usage of such method are shown.